Patients with suspected Lassa fever in London during 1984: problems in their management at St Thomas's Hospital. Issue 6508 (30th November 1985) - Tilzey, A J; Webster, M; Banatvala, J E
Abstract : During 1984, 23 patients in whom a diagnosis of viral haemorrhagic fever was considered presented to the accident and emergency department at St Thomas's Hospital. There were no confirmed cases of viral haemorrhagic fever. Nine patients were transferred to Coppett's Wood Hospital, the nearest specially designated high security isolation unit. Malaria was the final diagnosis in 14, and in six this diagnosis was confirmed only after examining repeated smears at Coppett's Wood Hospital. Transferral of patients to such units is time consuming, expensive, and often unnecessary. Specially designated isolation units in district general hospitals and all teaching hospitals would simplify and improve the care not only of patients with a possible viral haemorrhagic fever but also patients with tuberculosis, multiply resistant staphylococcal infections, and viral infections that may be hazardous if transmitted to immunocompromised patients.